Resuming professional football (soccer) during the COVID-19 pandemic in a country with high infection rates: a prospective cohort study - Schumacher, Y. O.; Tabben, M.; Hassoun, K.; Al Marwani, A.; Al Hussein, I.; Coyle, P.; Abbassi, A. K.; Ballan, H. T.; Al-Kuwari, A.; Chamari, K.; Bahr, R. (British Journal of Sports Medicine, 2021)
OBJECTIVES: The risk of viral transmission associated with contact sports such as football (soccer) during the COVID-19 pandemic is unknown. The aim of this study was to describe the infective and immune status of professional football players, team staff and league officials over a truncated football season resumed at the height of the COVID-19 pandemic in a country with high infection rates and to investigate the clinical symptoms related to COVID-19 infection in professional football players.